Effect of pH and storage conditions on measured ionised calcium concentration in dogs and cats. (22nd June 2020) - Mazaki‐Tovi, Michal; Topol, Shira; Aroch, Itamar
Abstract : Background: Aerobic blood sample collection and processing results in increased serum pH and decreased ionised calcium (iCa) concentration. This prospective study aimed to determine the effect of pH and storage conditions on measured iCa concentration in serum samples obtained from dogs and cats and establish correction formulas for use in samples obtained aerobically. Methods: Blood samples were collected from 44 dogs and 25 cats; iCa and pH were measured immediately under anaerobic conditions and in samples stored under several aerobic conditions. Results: Measured iCa concentrations were significantly lower in samples stored at all aerobic conditions than in samples handled anaerobically in both dogs and cats (P<0.01 for all). The largest and most clinically significant differences were noted in samples stored at −20°C for 30 days in both dogs (0.48 mmol/l; 95 per cent CI 0.40 to 0.55) and cats (0.40 mmol/l; 95 per cent CI 0.33 to 0.47). Correction formulas (corrected iCa=measured iCa+coefficient × (measured pH–7.41); coefficient=0.597 for dogs, 0.627 for cats) yielded good agreement between the corrected and the actual iCa concentrations. Conclusions: Samples for iCa measurement can be stored at either 4°C or −20°C for 24 hours. Storage at −80°C is recommended for longer storage time periods.